1984
DOI: 10.1136/bmj.288.6413.281
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two antihistamine drugs on actual driving performance.

Abstract: A double blind placebo controlled experiment was conducted measuring the effects of the centrally active antihistamine triprolidine and the peripherally acting antihistamine terfenadine on actual driving performance in a group of experienced women drivers.Triprolidine greatly impaired driving behaviour, whereas terfenadine did not. Triprolidine also impaired subjective and objective measures of mood and arousal, and despite an awareness that their driving was impaired while they were taking this agent subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 3 publications
4
23
0
Order By: Relevance
“…Betts et al [ 12] found that being aware o f deterioration in driving due to drowsiness from a centrally acting anti histamine cannot be compensated for. Although past research looking at C N S effects has not shown significant changes using diphenhydramine in 50-mg doses, the P R EP did show C N S changes.…”
Section: Subjective Feelingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Betts et al [ 12] found that being aware o f deterioration in driving due to drowsiness from a centrally acting anti histamine cannot be compensated for. Although past research looking at C N S effects has not shown significant changes using diphenhydramine in 50-mg doses, the P R EP did show C N S changes.…”
Section: Subjective Feelingsmentioning
confidence: 99%
“…In a study comparing a centrally acting antihistamine, triprolidine (in the same class as diphenhydramine), and a peripherally acting antihistamine, terfenadine, on actual driving performance, triprolidine significantly impaired driving while terfenadine did not [12]. Specifically, time to complete the driving course and the number o f driving errors increased, as well as the inability to negotiate nar row passages.…”
mentioning
confidence: 99%
“…Whereas enhancement of sleep at night by promethazine 20 mg is paralleled by impaired daytime psychomotor function after a 25 mg dose (Hindmarch & Parrott, 1978), it may be predicted from our present negative findings that daytime psychomotor testing with temelastine 100 mg would fail to show impairment. It is noteworthy that terfenadine, a histamine Hl-receptor antagonist, has been reported not to speed sleep onset (Roehrs et al, 1984), nor to cause impairment on a daytime driving task (Betts et al, 1984).…”
Section: Methodsmentioning
confidence: 99%
“…Tripolidine has been shown to impair driving behavior, as well as causing subjective and objective measures of mood and arousal [4]. Reports on performance showed that reaction time was prolonged.…”
Section: Introductionmentioning
confidence: 99%